Economic Impacts of Citrus Greening (HLB) in Florida, 2006/07–2010/11 - Alan W. Hodges; Thomas H. Spreen (EDIS)
Since 2006, the bacterial disease citrus greening has cost Florida’s economy an estimated $3.636 billion in lost revenues and 6,611 jobs by reducing orange juice production, according to the study reported in this 6-page fact sheet written by Alan W. Hodges and Thomas H. Spreen, and published by the UF Department of Food and Resource Economics, January 2012.